Obesity, insulin resistance and type 2 diabetes mellitus in adolescents - Pajuelo Ramírez, Jaime (2018)
Introduction. Obesity is considered a public health problem. Its presence at an early age implies an obligation to identify the onset of complications such as insulin resistance and diabetes mellitus (DM). Methods. Observational, descriptive and transversal study. Participated 1206 teenage women. Obesity was defined with BMI values ≥95p according WHO. Serum levels of insulin, glucose and lipid profile were determined. T≥≤h e43 0,H1 m6o mgto/ed odLse,t fahinsigiesh i MnCso-uLdlDeinlL o r≥ef sA 1iss3tsa0en smcmege (/n Rdt IIL)n. daFneodxr (hdHyyOpsleMiptrAiidg-eIl)ym cwieaarssid: uehsmyepidae, r≥ucsh 1ion3lge0 s tmhteegr o/MdleaLmt.t hTiaeh we≥ so 2be0qe0su eam ttigeo/endn wLa,ig tlheo rwtsh ewH viDtahLl u-RCeI underwent an oral glucose tolerance test (PTG): glycemia of 140 to 199 mg / dL intolerant to glucose and ≥ 200 mg/dL as diabetic. Results 25,1% (303) of the population was obese; 246 obese adolescents participated in the biochemical evaluation, 28,1% (69) of them presented RI. In the obese teenagers with and without IR, the average of the biochemical variables in the former were higher, these differences being statistically significant, except for HDL-C. Differences between the prevalence of dyslipidemias were significant except for HDL-C. The IR presented an OR of 10,9 (CI 5,4-26,6), 12,1 (CI 4,9-30,1), and 7,6 (CI 3-19,5) with hypertriglyceridemia, hypercholesterolemia and high LDL-C. The PTG showed 3,3% intolerant and none diabetic. Conclusions: 28,1% (69) of obese adolescents presented RI; no study participant presented DM.